PERFORMANCE OF ASPHALT CONCRETE USING SUPERPAVE (SUPERIOR PERFORMING ASPHALT PAVEMENT) AGGREGATE GRADATIONS - Faisal
The Strategic Highway Research Program (SHRP) in the USA has developed a new specification for asphalt mix gradation that is called Superpave. Five aggregate gradings, classified in terms of nominal maximum aggregate particle size, are specified. A major feature of the gradation is a restricted zone from which the gradation is excluded. This thesis describes a laboratory investigation of asphalt concrete binder course mix containing five different aggregate gradings, all within the envelope specified by Superpave for a 19 mm nominal maximum size aggregate; one grading passed through the restricted zone. In addition mix prepared to the median of the Bina Marga (BM) envelope specified for the material (Grading Type V) was investigated. Marshall analysis showed that the optimum bitumen content was lowest for the BM gradation (5.5%) and highest for the mix prepared at the lower (coarser) limit of the Superpave gradation (5.9%). Mixes at all gradations satisfied The Asphalt Institute mix design criteria and there was no evidence to suggest that the mix made to the gradation that passed through the restricted zone was significantly inferior to other mixes. All of the mixes satisfied the BM criterion for resistance to water damage. Mixes prepared at optimum bitumen content were tested for indirect tensile strength (static load), resistance to permanent deformation in the wheel tracking test and workability index using the gyropac test. The best performance in these tests was recorded for the mix prepared to the BM gradation while the mix prepared at the lower limit of the Superpave gradation showed the worst performance; data determined for mixes prepared at the other three Superpave gradations tended to cluster midway between these extremes. Again there was no evidence to suggest that unsatisfactory performance could be expected from mix prepared to the gradation that passed through the restricted zone. In the investigation, specimens were prepared and analysed according to the Marshall procedure. The Superpave specification is based on samples prepared by gyratory compaction and this procedure should be followed in future investigations .